The Flexural Behavior of Reinforced Ultra-High Performance Engineering Cementitious Composite (UHP-ECC) Beams Fabricated with Polyethylene Fiber (Numerical and Analytical Study) - Ahmed M. Yassin; Mohamed Ahmed Hafez; Mohammad Mohie Eldin (Buildings)
Ultra-high performance engineered cementitious composite (UHP-ECC), which is a new and ductile version of concrete, has attracted researchers recently due to its exceptional mechanical properties: its very high compressive strength (from 100 to 200 MPa) and very high tensile strain capacity (not less than 3% and up to 8%). However, the available experimental literature is small due to its very high cost. To overcome the high cost of the experiments of UHP-ECC, the finite element modeling package ANSYS was used to create a new modeling technique using the Menetrey–Willam constitutive model, recently added to ANSYS. This technique was validated using previous experimental results for UHP-ECC beams and found to be accurate and effective. The previous FE model was used to conduct a parametric study and the variables—the compressive strength of the concrete, the percentage of the volume content of polyethylene fibers, the tensile reinforcement ratio, and the span-to-depth ratio—were found to be effective upon the flexure behavior of the reinforced UHP-ECC beams. As the analysis and design of UHP-ECC beams fabricated with polyethylene fiber are not available yet through design codes, an analytical model including some equations was deduced to calculate the flexure capacity of such beams. The results of the parametric study were used to investigate the validity and accuracy of the analytical model. The proposed equations demonstrated a good estimation compared with the numerical analysis results.